(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Hydatidosis is a zoonotic infection due to larval stage of the tapeworm echinococcus. In adults’ liver represents the prevalent site and lungs are the second commonest site. Although these are common sites, it can occur at any site including spleen, pancreas, peritoneum, retroperitoneum, central nervous system, soft tissues, and breast. We present the histopathological spectrum of hydatid cyst at unusual sites in our hospital over a period of three years. The present retrospective study was conducted in the department of Pathology, SKIMS during a period of 3years from July 2019 to June 2022 where a total of 12cases were diagnosed as Hydatid Cyst at unusual sites on HPE during study period were included. Male and female ratio of incidence found to be 1:1:4. Maximum no of cases i.e., 3 occurred in brain, 2 in spleen,2 in thigh,1 each in breast, omentum, kidney, sacral ala and mediastinum.The hydatid cyst can be present in any part of the body and there is no natural immunity that inhibit the development & growth of it. These unusual locations frequently result in nonspecific symptoms. To avoid life-threatening complications and unnecessary radical surgeries, hydatid cystic disease should always be suspected in all cystic lesions of radio imaging investigations, especially in endemic areas.